New qualitative perspective in students’ English presentation skills in China-developing a student-based module - Sun, Lifang; Ismail, Hanita Hanim; Aziz, Azlina Abdul (Institute of Advanced Engineering and Science, 2025)
Since English is the world’s lingua franca, English learners need to master communication skills to succeed in their respective fields. However, Chinese college students face the problem of separation between learning and using what they learned in the traditional English classrooms. This study aims to explore the university students’ needs of English presentation learning. The research questions are: i) What are the students’ language needs to improve an English presentation? ii) What are the skills needed when doing an English presentation? and iii) What are the students’ preferences in English presentation class? The researchers conducted focus-group interviews (FGI) which were participated by 30 students and semi-structured interview for five teachers to understand the students’ real needs and preferences in the process of learning English speaking. Three themes were generated by axial coding from the interview data: i) English language needs; ii) presentation skills’ needs; and iii) students’ preferences.The findings can help the teacher design the English-speaking class more effective and have adjustments according to students’ real productions using production-oriented approach in English presentation teaching.